Comparison of Hysterosalpingography With Laparoscopy in the Diagnosis of Tubal Factor of Female Infertility - Tan, Jifan; Deng, Min; Xia, Meng; Lai, Muhua; Pan, Wenwei; Li, Yubin (Frontiers in Medicine, 2021)
Background: Laparoscopy is considered to be the gold standard in the evaluation of causes leading to infertility. Hysterosalpingography (HSG) permits indirect visualization of the cervical canal, uterine cavity, and tube patency, which is helpful for evaluating the causes of infertility. Objective: This study aimed to detect tubal abnormalities in infertile women by HSG or laparoscopy and determine the value of HSG in diagnosing fallopian tube status. Methods: The study group consisted of 1,276 patients. HSG was performed as a preliminary test for the evaluation of fallopian tube status. Women were subjected to laparoscopic examination on evidence of HSG abnormalities. Results: The negative predictive value of HSG for detecting patency or occlusion for the right/left tube was 92.08 and 95.44%, respectively. The kappa values for the consistent diagnosis in the right/left tube were 0.470 and 0.574, respectively. In cases of low patency of the right/left tube, there was a greater than a 40% chance for the tube to be patent, and the remaining high probability was pelvic adhesion. The positive predictive value of HSG for detecting patency or occlusion for both tubes was 87.2%. The kappa value was 0.898 [95% CI (0.838, 0.937), p < 0.001], which meant that the diagnostic accuracy of HSG for both tube patency/occlusion was explicit. The kappa value for the diagnosis of hydrosalpinx (especially for bilateral tube hydrosalpinx) was 0.838 [95% CI (0.754, 0.922), p < 0.001], and the diagnostic accuracy for HSG was 79.8, 67.9, and 72.4%, respectively. Conclusion: The current study concluded that HSG is a good diagnostic modality to detect tube abnormalities in infertile patients. HSG and laparoscopy are complementary to each other and whenever the patient is undertaken for diagnosis of infertility. Cost-effective HSG had good predictive value in identifying tubal factor infertility.